Weight loss-induced changes in adipose tissue proteins associated with fatty acid and glucose metabolism correlate with adaptations in energy expenditure. Issue 1 (December 2015) - Camps, Stefan; Verhoef, Sanne; Roumans, Nadia; Bouwman, Freek; Mariman, Edwin; Westerterp, Klaas
Abstract Background Energy restriction causes adaptations in energy expenditure (total-, TEE; resting-, REE; activity induced-, AEE). Objective To determine if changes in the levels of proteins involved in adipocyte glucose and fatty acid metabolism as indicators for energy deficiency are related to adaptations in energy expenditure during weight loss. Methods Forty-eight healthy subjects (18 men, 30 women), mean ± SD age 42 ± 8 y and BMI 31.4 ± 2.8 kg/m2, followed a very low energy diet for 8 wk. Protein levels of fatty acid binding protein 4 (FABP4), fructose-bisphosphate aldolase C (AldoC) and short chain 3-hydroxyacyl-CoA dehydrogenase (HADHsc) (adipose tissue biopsy, western blot), TEE (doubly labeled water), REE (ventilated hood), and AEE were assessed before and after the 8-wk diet. Results There was a positive correlation between the decrease in AldoC and the decrease in TEE (R  = 0.438, P  < 0.01) and the decrease change in AEE (R  = 0.439, P  < 0.01). Furthermore, there was a negative correlation between the increases in HADHsc and the decrease in REE (R  = 0.343, P  < 0.05). Conclusion The decrease in AldoC correlated with the decrease in AEE, which may be explained by a decreased glycolytic flux. Additionally, the change in HADHsc, a crucial enzyme for a step in beta-oxidation, correlated with the adaptation in REE. Trial registration Clinical Trial Registration Number:NCT01015508 at clinicaltrials.gov